PENINGKATAN KUALITAS PESERTA DIDIK MELALUI PENANAMAN PENDIDIKAN KARAKTER DALAM PROSES PEMBELAJARAN - Ketut Bali Sastrawan (Maha Widya Bhuwana: Jurnal Pendidikan, Agama dan Budaya, 2018)
Through the learning process, it is expected to insert character education because it isvery important to be developed in schools, with the ability to form the character of students canbe well directed because students are an important aspect that determines the progress of thenation. In character education in schools, all the components (stakeholders) should be involved.Ideally, education should not only encourage students to develop talents that are tailored to thescience within the school, will education also mandatory to improve the quality of human beingswho are believers and cautious to God Almighty, personable, intelligent, creative, and disciplined.Character education is a planned effort to make learners recognize, care and internalize thevalues so that learners berkaraker, where the goal of character education is to improve thequality and implementation of education in schools through the formation of the character oflearners intact, integrated, and balanced, appropriate Standard.